Intoxicação natural e experimental por Portulaca oleracea e Leucaena leucocephala em pequenos ruminantes. - Oliveira, Alexandra Melo (2020)
In the Northeast of Brazil, losses of animals due to poisoning plants are frequent. Knowledge of toxic plants, clinical conditions and injuries associated with their ingestion is important for preventive measures. In this essay, two natural outbreaks of plant poisoning occurred in the State of Paraíba - Brazil, are shown. One of them, associated with the ingestion of Portulaca oleracea in goats and sheep and the other due to the ingestion of Leucaena leucocephala by goats. The results of the experimental reproductions of intoxications are also exhibited. A total of 160 animals, from a herd of approximately 1000 heads of sheep and goats, died in the municipality of Congo-Paraíba following access to areas invaded by Portulaca oleracea. The tests realized to determine the amount of nitrates, performed on plants harvested from grazing areas, were positive. In the experimental intoxication two goats received Portulaca oleracea, in a single dose of 40 g / kg. The manifested signs were tachycardia, dyspnoea, mydriasis, vocalization, nystagmus, abdominal distension, ruminal atony, cyanotic mucous membranes, muscle tremors, salivation, incoordination, falls, decubitus, pedaling movements and death. At necropsy, as mucous membranes were cyanotic, blood clotted rapidly and was dark brown in color. The diphenylamine test was positive in the ruminal content and blood. The presence of large areas occupied by the plant, with nitrate concentration above 2%, justified the high number of deaths, so, this is one of the biggest outbreaks of mortality due to ingestion of toxic plants reported in the semi-arid of Brazil. The natural outbreak of Leucaena leucocephala poisoning occurred in the municipality of Arara-Paraíba. Ten adult goats had access to the leaves and fruits cut from the trees. The following day two animals showed excessive salivation, tremors, incoordination, foamy salivation, difficulty in grasping food and lip tremors. Subsequently, the animals shed hair and the owner opted for the commercialization of the animals. Experimental intoxication was carried out on a male goat, six months old, 15 kg. Leucaena leucocephala was offered fresh, exclusively and ad libitum, for 18 days. In the experimental reproduction clinical signs were identified days after the consumption of the plant. Hypothyroidism, elevations in liver enzymes and reduced creatinine were identified. The animal was euthanized in extremis when it presented severe weakness. Edemas and ulcerations were seen in several organs. The history of the case, the signs preceded by the animals and an experimental reproduction proved the acute intoxication by Leucaena leucocephala in goats. The manifestation of symptoms was faster than recorded by other authors, arising with neurological signs in the outbreak. In addition to the signs identified in cases of intoxication, there was a loss of vocalization in experimental reproduction. The absence of sperm in the seminiferous tubules was an alteration also identified and which had not yet been reported in previous studies, which may be related to the interference of mimosina in the reproductive sphere. Natural and experimental ingestion of the plant produced intoxication in the goat species and suggested high toxicity of the plants in the region.